Neuroimmune aspects of mood, anxiety and cognitive effects of leads/drug candidates acting at GABAA and/or sigma-2 receptors: In vitro/in vivo delineation by nano- and hiPSC-based platforms - Savić, Snežana; Pantelić, Ivana; Jančić, Ivan; Savić, Miroslav (Archives of Pharmacy, 2022)
Mood, anxiety and cognitive symptoms in psychiatry and neurology represent a significant worldwide burden. Due to difficulties in disease modeling and drug delivering to the site of action, as well as gaps in in vitro/in vivo extrapolation, the efforts to elucidate the roles of stress and neuroimmune pathways in both, etiology and therapy of these symptoms are challenging, but may nevertheless result in novel mechanisms of action. Recent preclinical studies provided novel leads/drug candidates with promising mood, anxiety and cognitive effects, the intellectual property rights of which are co-owned by the project beneficiary. We aim to: (1) incorporate the selective ligands of GABAA and/or sigma-2 receptors, with code names GL-II-73, DK-I-56, MM-I-03 and CW-02-79, together with two reference sigma-2 receptor ligands (siramesine and RHM-1), into the optimized nanoparticles and target their delivery to the human induced pluripotent stem cell (hiPSC)- based tri-culture cell neuroinflammation model, or rat brain; (2) quantify the immunological/morphological/neurochemical markers in immunologically challenged hiPSC-derived neurons, astrocytes and glia cells, and (3) assess their effects on behavior and biological markers in immunologically challenged animals of both sexes subjected to chronic mild unpredictable stress. We assume that the targeted nanodelivery of selected compounds to the brain will improve their pharmacokinetic profile, fortify their beneficial effect on mood, anxiety and cognition, and help delineate the contributing neuroimmune effects presumably arising mainly from microglia. The familiarization with neuroimmune aspects and pharmacokinetic optimization will support the preclinical progress of these compounds and might provide a rationale for designing clinical trials.